A network aware based recommender system for VOIP application service in eLearning environment / Nazdiana Ab. Wahab - Ab. Wahab, Nazdiana (2009)
The varying bandwidth availability of a network path, has contributed to the unstable performance when running audio and video services over the internet network. VOIP application integration in eLearning system, which offers voice and video services, is one example of applications that has been affected by this varying network availability. To minimize this impact, a network based algorithm that could provide current network status on bandwidth availability, and then do the recommendation accordingly is needed. Therefore, this dissertation work, proposed a network based recommender that could be used in the application of VOIP services in eLearning environment. This paper showed the integration of VOIP in a simple eLearning prototype system. A network aware based algorithm is used to recommend users the best VOIP services available at that point of time (whether audio, video or data) based on the real time data obtained from bandwidth measurement tool. Pathload has been chosen as a measurement tool that estimates the available bandwidth of a network path.